TINGKAT HEMOGLOBIN LANSIA: PERBEDAAN PENGUKURAN ANTARA DUA ALAT BERBEDA - Diah Prihatiningsih; I Gusti Putu Agus Ferry Sutrisna Putra (PT. Jurnal Center Indonesia Publisher, 2024)
The examination of hemoglobin levels in the elderly is crucial as iron deficiency or anemia is often found in this age group. Various methods of hemoglobin examination are used in healthcare facilities. This study aims to identify the differences in hemoglobin levels using the Dirui BCC-3600 and Quick Check devices in the elderly population at Puskesmas Biromaru. This research is descriptive-comparative in nature. The sample consisted of 30 patients undergoing hemoglobin examination at the Puskesmas Biromaru laboratory between March 29th and April 30th, 2023. The sampling method used was accidental sampling, with venous blood samples from 30 respondents. The results of the study showed that the average hemoglobin level using the Dirui BCC-3600 device was 12.86 g/dL, while with the Quick Check device it was 11.77 g/dL. Normality testing was conducted using the Shapiro-Wilk test, which yielded a p-value of 0.023. A p-value < 0.05 indicates non-normal data distribution, thus followed by the Mann-Whitney test. The Mann-Whitney test resulted in a significant value (p) = 0.011. In conclusion, there is a significant difference in hemoglobin levels using the Dirui BCC-3600 and Quick Check devices in the elderly.